Perancangan Perangkat Lunak Pengenkripsian Citra BMP,GIF dan JPG dengan Menggunakan Metode HILL - Abdul Halim Hasugian, M.Kom (UIN Sumatera Utara, 2017)
Digital image can be defined as a function of two variables, f (x, y), where x and y are spatial coordinates and the value of f (x, y) is the image intensity at the coordinates. Digital images represent image data in numbers representing the level of gray (color black and white) or color coordinates (color image). The problem in this system is how to implement digital image cryptography using Hill Chiper method so as to ensure the security of the digital image from the parties which is not entitled to know it or make changes in the digital image. This digital image cryptography is designed using Hill Chiper method implemented with Visual Basic 6.0 programming language. Hill Chip method is a Hill Cipher method is one of the symmetric key cryptography algorithms. Hill Cipher algorithm uses an m x m matrix as the key for encryption and decryption. The basic matrix theory used in Hill Cipher is inter-matrix multiplication and inverse in matrix. This digital image cryptography produces an obscure and invisible digital image without the help of the software that the author designs, and changes the size of the digital image file by mapping the RGB value of each pixel of the digital image into a geometry . However, this system can only encrypt digital imagery with JPG, BMP, and GIF formats so it still needs further development. Keywords: Cryptography, Digital Imagery and Hill Chiper Method